On the Time of Control for the Brown Planthopper, Nilaparvata lugens STÅL - KISIMOTO, Ryoiti; MORIYA, Shigeo; NAGATA, Toru; MAEDA, Yoichi (Japanese Journal of Applied Entomology and Zoology, 1973)
Suitable time of insecticide application was tested in relation to the seasonal prevalence of the brown planthopper. Population growth of the brown planthopper in rice field begins with macropterous immigrants from the late June to the middle of July (the 2nd adult period of the year), followed by two generations in which eggs to be source of the next generation are laid by brachypterous females from the end of July to the middle of August (the 3rd adult period) and from the end of August to September (the 4th adult period). Hopperburns appear mostly from the end of September to October along with growing of nymphs produced by the 4th period adults. Controls in later seasons are often little effective because of survival of eggs from insecticides, owing to wide and overlapping generation. It was proposed to advance controlling time and to eliminate the brachypterous females. Times of treatment were selected as follows, the beginning (treatment I), the peak (II) and the end (III) of the 3rd adult period and the beginning of the 4th adult period (IV). Mipcin® fine granule (o-cumenyl methylcarbamate), 4kg per 10a, was applied once in each treatment. In treatment I population density of the planthopper was depressed sufficiently through the growing period of rice plant and a high yield was obtained. Good result was obtained also in treatment IV. However, in treatment II and III early recovery of population density due to survived eggs caused heavy infestation and severe hopperburns. The residual effect of Mipcin used seemed to be not sufficient to cover the incubation period of the planthopper egg of about 10 days.